Neuroprotective potential of Vicia faba seed extract in haloperidol-induced Parkinsonian rats (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2026)
Parkinsonian disorders are characterised by dopaminergic depletion and motor dysfunction, prompting growing interest in plant-derived dopamine precursors as supportive therapies. Although Vicia faba L. seeds are known to contain L-DOPA, evidence linking standardised extracts to functional neurobehavioral improvement, together with demonstrated central dopaminergic activity, remains limited. This study aimed to evaluate the neurobehavioral efficacy of a standardised hydro-alcoholic V. faba seed extract and assess its dopaminergic contribution in a haloperidol-induced Parkinsonian rat model. Extract-treated animals showed progressive improvements in paw withdrawal latency, locomotor activity, and exploratory behaviour across treatment levels compared with disease controls, with paw withdrawal time showing strong statistical significance (p